Uso de coleiras impregnadas com deltametrina 4% em cães no controle da leishmaniose visceral - Kazimoto, Thais Aparecida (Universidade Federal Rural do Semi-Árido, 2016)
Visceral leishmaniasis (VL) is a potentially fatal chronic disease when left untreated. In Brazil, is caused by the protozoan Leishmania infantum is transmitted primarily by sandfly Lutzomyia longipalpis, the dog as the main reservoir. The control of this disease has been in a challenge to public health, and as a proposal for a measure of control of canine VL using dog collars impregnated with deltamethrin to 4% in dogs. Thus, the research aims to assess the effectiveness of these collars on the prevalence of canine VL and infection rate of sandfly to L. infantum in endemic areas for VL. The survey was conducted in two areas equidistant from the city of Mossoró/RN, with similar environmental characteristics. In both of these areas were carried out two surveys every six months and to serologic canines are search for a year, and in a were performed only the procedures mentioned above, being named Control Area (AC) and the other, in addition to the steps mentioned earlier were also carried out two collaring dogs with collars impregnated with deltamethrin the 4% that occurred every six months This area was named “Encoleiramento” Area (AE). For diagnosis of canine VL was made DPP and ELISA. The analysis of the prevalence of canine VL was carried out through the Chi-square test and the incidence rate of the disease through the Odds ratio. For the collection of sandflies were selected three houses in each of the areas, the insects were collected monthly using CDC light traps and separated by species, sex, stage of investigation and research. The morphological identification of sandflies and the females were subjected to real-time PCR for the detection of DNA of L. infantum. With regard to prevalence and incidence rates of VL, evaluating the areas in isolation, one could observe that the use of dog collars was able to reduce the prevalence of the disease in AE and 53 to 59% reduction in the risk of illness. As the sandfly, collected the species L. longipalpis, L. evandroi, L. cortelezzii and L. migonei, with 81,8% % L. longipalpis. Positive pools were obtained from L. longipalpis of AE only during the first investigation while in AC could observe the presence of DNA of the parasite in vector in both investigations. Based on the results, the use of impregnated with deltamethrin collars to 4% has the potential to reduce the prevalence of canine VL as well as allows a reduction in at least 53% the risk of illness. It is also possible to suggest that the continued use of these dog collars can have the potential to reduce the rate of infected sandflies. Thus, impregnated with deltamethrin collars to 4% can be indicated as a control measure for the disease, together with other measures currently recommended
Keywords: Leishmania infantum; Reservatório de doenças; Zoonoses; Prevenção & controle; Inseticidas; psychodidae; Leishmania infantum; Diseases reservoirs; Zoonosis; Prevention & control; Endemics; Insecticides; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE